1999
DOI: 10.1111/j.1574-6968.1999.tb13561.x
|View full text |Cite
|
Sign up to set email alerts
|

The 40- and 90-kDa membrane proteins (ORF6 gene product) ofMycoplasma pneumoniaeare responsible for the tip structure formation and P1 (adhesin) association with the Triton shell

Abstract: After Triton X-100 treatment of Mycoplasma pneumoniae cells, a portion of the adhesin P1 (transmembrane protein) proved to remain tightly associated with the Triton insoluble material (Triton shell) as shown previously by several authors. However, the spontaneous loss of two cytadherence-associated membrane proteins of 90 and 40 kDa (gene product of the open reading frame 6 of the P1 operon) in a hemadsorption-negative mutant, designated M5, resulted in a 100% release of the P1 protein into the Triton phase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…However, the lack of the ORF6 gene product in a spontaneous haemadsorption-negative mutant resulted in the release of all the P1 protein into the Triton-soluble phase (Layh-Schmitt & Harkenthal, 1999). These findings suggest that the ORF6 gene product may be responsible for proper disposition of the P1 molecules in the mycoplasma membrane, which seems to be a prerequisite for interaction of the 40 and 90 kDa cytadherence-associated proteins and the P1 protein with the cytoskeleton.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, the lack of the ORF6 gene product in a spontaneous haemadsorption-negative mutant resulted in the release of all the P1 protein into the Triton-soluble phase (Layh-Schmitt & Harkenthal, 1999). These findings suggest that the ORF6 gene product may be responsible for proper disposition of the P1 molecules in the mycoplasma membrane, which seems to be a prerequisite for interaction of the 40 and 90 kDa cytadherence-associated proteins and the P1 protein with the cytoskeleton.…”
Section: Introductionmentioning
confidence: 72%
“…The results indicate that clustering of the P1 adhesin together with the adhesin-related 30 kDa protein and the cytadherence accessory proteins of 40 and 90 kDa in the membrane of the characteristic terminal structure of the cell is essential for effective attachment of M. pneumoniae to its host cell. The 40 and 90 kDa proteins and the cytoskeleton-forming proteins HMW1-HMW3 are required for tip structure formation and clustering of the P1 protein in the tip, as spontaneous cytadherence-negative mutants lacking the 40 and 90 kDa protein or HMW1-HMW3 exhibit a round or ovoid morphology without a distinct terminal organelle (Baseman et al, 1982 ;Hahn et al, 1998 ;Layh-Schmitt et al, 1995 ;Layh-Schmitt & Harkenthal, 1999). Moreover, these mutations resulted in a random distribution of the P1 protein in the mycoplasma cell membranes, suggesting an intimate interaction of the P1 protein, not only with the 40 and 90 kDa proteins, but also with one or more of the HMW1-HMW3 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Our electron microscopy studies revealed that the typical flask-shaped appearance of M. gallisepticum , presenting a defined single knob-like structure at one polar end, changed to a rounder, bulkier morphology, with less defined tip structures in strains lacking GapA and CrmA. Similarly, M. pneumoniae mutant M5 which had lost the homolog of CrmA exhibits a perfect round cell shape, but has lost the tip-like structure [ 53 ]. Mutants of M. pneumoniae lacking homologs of GapA and CrmA also have lost the elongated flask-shape and display a branched cell morphology [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insertion of P1 into the membrane and its trafficking to the attachment organelle is largely dependent on P90 and P40 [38,39,40]. Mutants defective in the expression of P90 and P40 allow P1 to completely partition to the Triton X-100 soluble phase.…”
Section: Introductionmentioning
confidence: 99%
“…Mutants defective in the expression of P90 and P40 allow P1 to completely partition to the Triton X-100 soluble phase. In wild type cells, P1 typically partially associates with the Triton X-100 insoluble shell [39]. Mutants unable to produce mpn142 are defective in cellular adherence because P1 cannot traffic to the tip structure resulting in random P1 distribution around the cell body [38,40].…”
Section: Introductionmentioning
confidence: 99%